Real-life data on improvement of survival after perioperative chemotherapy versus surgery alone on resectable adenocarcinoma of the stomach – a single-center study - Kuhnle, Philipp Johannes; Israel, Karl-Friedrich; Menges, Markus (Zeitschrift für Gastroenterologie, 2019)
Background In the last decade, neoadjuvant chemotherapy has become the standard of care also for curatively resectable advanced gastric cancer. Prospective randomized studies have shown a significant benefit in disease free and overall survival rate after perioperative chemotherapy as compared to immediate surgery. However, data in the “real-life” setting are rare. In our retrospective study, we wanted to clarify the question whether this benefit is achievable under real-life conditions.Methods A total of 81 patients with resected adenocarcinoma of the stomach or distal esophagogastric junction (AEG III) clinical stage II–IIIc according to UICC (eighth edition) were enrolled. Forty-two patients received perioperative chemotherapy (cohort 1) and 39 patients were operated on immediately (cohort 2). Chemotherapy was carried out according to the ECF, EOX, or FLOT protocols.Results Overall 5-year survival was 35.7 % in cohort 1 and 23.7 % in cohort 2. Thus, the relative 5-year overall survival benefit was 51 %, and 12 % in absolute numbers (p = 0.083). For patients receiving perioperative chemotherapy per protocol (n = 20), a more marked absolute improvement in 5-year overall survival of 16.3 % as compared to immediately operated on patients was achieved (p = 0.05). Progression-free survival in this analysis was shown to be improved by perioperative chemotherapy also without statistical significance (p = 0.03).Conclusions Patients with curatively resectable gastric adenocarcinoma or type III AEG tumor benefit from perioperative chemotherapy in terms of overall survival even under real-life conditions. Moreover, a benefit in progression-free survival can be demonstrated.
Keywords: gastric cancer; gastric adenocarcinoma-neoadjuvant chemotherapy; perioperative chemotherapy; real-life data